Pembuatan Sistem Lapor Komdisma Berbasis Web di Komisi Disiplin dan Kemahasiswaan SV IPB - Nabila Fakhiratunisa; Merry Ardelia Wirastuti; Kaisar Renaisance Al-Ars; Diana Putri Rahmani; Mochamad Farras Fauzan; Naufal Alif Falah; Joddy Lintar Balle; Mira Fitria Dewi; Tria Febriyanti; Vandame Ronald Suhada; Gema Parasti Mindara; Ridwan Siskandar (Jurnal Sains Indonesia, 2021)
Rapid technological advances affect the workings of individuals, organizations and companies. Komisi Disiplin dan Kemahasiswaan (Komdisma) SV IPB is a team of lecturers whose job is to monitor student discipline. In order to carry out its duties, Komdisma received reports of violations committed by students. However, the process of reporting student violations is still manual using books and paper, resulting in incompatible data, duplicate data, and the time to search and recap data. For this reason, a computerized information system is needed that supports the business process of reporting student violations so that business processes can run more efficiently. The purpose of making this web-based information system is to provide convenience and assist Komdisma in recording student violations so that the violation reporting process takes a relatively short time and produces reliable data.